Penurunan Angka Kematian Ibu dan Anak di Kabupaten Brebes: Sebuah Narrative Review Strategi Daerah - Rike Dianita; Bambang Budi Raharjo; Nuke Prasetyani Nurhayati (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Maternal and child mortality remains a major public health challenge in Indonesia, with Brebes Regency identified as one of the regions with a relatively high burden. This study aims to provide a narrative review of strategies implemented to reduce maternal and child mortality in Brebes, while highlighting their relevance within the broader Indonesian health policy framework. Literature from peer-reviewed journals indexed in Scopus and Web of Science, published between 2019 and 2024, was reviewed. The findings indicate that strategic planning at the district level emphasizes strengthening the role of midwives, improving access to primary health services, and integrating local programs with national policies. Behavioral nutrition interventions, such as the Baduta Program, and community-based innovations, such as “Buaian Services,” have shown potential in improving maternal and child health outcomes. However, challenges persist in the form of limited resources, disparities in service quality, and cultural barriers to health-seeking behavior. This review underscores the importance of combining top-down policy approaches with bottom-up community-driven initiatives. Future research is recommended to adopt mixed-method designs for a more comprehensive evaluation of program effectiveness.